2021
DOI: 10.1089/neur.2021.0043
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Time-Domain Cerebrovascular Reactivity Metrics and Discriminate Capacity for the Upper and Lower Limits of Autoregulation: A Scoping Review of the Animal Literature

Abstract: Over a wide range of systemic arterial pressures, cerebral blood flow (CBF) is regulated fairly constantly by the cerebral vessels in a process termed cerebral autoregulation (CA), which is depicted by the Lassen autoregulatory curve. After traumatic brain injury (TBI), CA can get impaired and these impairments manifest in changes of the Lassen autoregulatory curve. Continuous surrogate metrics of pressure-based CA, termed cerebrovascular reactivity (CVR) metrics, evaluate the relationship between slow vasogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…While COx_a utility remains in its infancy, there is a growing literature body that evaluates the similarity between NIRS-based cerebrovascular reactivity measures and the more standard PRx [25][26][27][28][29][30]. This is evidenced by pre-clinical literature providing only validation for ICP and NIRS-based cerebrovascular reactivity indices as true measures of the lower limit of autoregulation in several different animal models [31]. This strong association between NIRS and cerebral blood flow/cerebral blood volume is also supported by the growing objective body of literature supporting a moderate/strong correlation between NIRS measures and cerebral blood flow [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While COx_a utility remains in its infancy, there is a growing literature body that evaluates the similarity between NIRS-based cerebrovascular reactivity measures and the more standard PRx [25][26][27][28][29][30]. This is evidenced by pre-clinical literature providing only validation for ICP and NIRS-based cerebrovascular reactivity indices as true measures of the lower limit of autoregulation in several different animal models [31]. This strong association between NIRS and cerebral blood flow/cerebral blood volume is also supported by the growing objective body of literature supporting a moderate/strong correlation between NIRS measures and cerebral blood flow [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has established that the cerebral oximetry index (COx_a), which assesses the slow wave vasogenic changes between near-infrared spectroscopy (NIRS) based regional brain tissue oxygenation (rSO 2 ) and ABP, is comparable to PRx [25][26][27][28][29][30]. Similarly, the COx_a indices have been shown in pre-clinical literature to measure aspects of the Lassen autoregulatory curve [31][32][33][34][35][36]. This non-invasive measure of cerebrovascular reactivity determination opens the potential to evaluate cerebral autoregulation in non-TBI cohorts, and explore personalized cerebral physiologic targets focused on neuroprotection in such populations.…”
Section: Introductionmentioning
confidence: 99%
“…The CVR metrics are defined as moving Pearson’s correlation coefficients between slow-wave (i.e., 0.05–0.005 Hz) ( Howells et al, 2015 ) fluctuations in a driving pressure for CBF, such as CPP/MAP, and a surrogate for pulsatile CBV/CBF, such as oxyhemoglobin (HbO), deoxyhemoglobin (HHb) or rSO 2 ( Lee et al, 2009 ; Brady et al, 2010 ; Zweifel et al, 2010b ; Zeiler et al, 2017a ; 2017b ; Mathieu et al, 2020 ; Gomez et al, 2021a ; Gomez and Zeiler, 2021 ; Zeiler, 2021 ). These NIRS-based indices have been validated in animal models to accurately detect the LLA ( Brady et al, 2008 ; 2010 ; Lee et al, 2009 ; Sainbhi et al, 2021 ) and clinical data support associations with ICP based cerebrovascular reactivity measurement through rough estimates ( Zweifel et al, 2008 ; 2010a ; Zeiler et al, 2017a ; 2017b ). However, further work is required to understand the importance of NIRS-based cerebrovascular indices.…”
Section: Introductionmentioning
confidence: 94%
“…Preclinical models are scarce to validate these measures against the Lassen autoregulatory curve. A recent systematically conducted scoping review from our group has demonstrated that most measured indices, namely ICP and NIRS based metrics, were able to accurately distinguish CPP/MAP from above and below the LLA in pre-clinical models ( Sainbhi et al, 2021 ). However, none of the studies were able to assess the ULA due to cardiac failure at higher CPP/MAP in these animal models ( Sainbhi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, literature assessing the association between continuous CA metrics and NIRSbased rSO 2 delivery is underdeveloped. 79,[89][90][91][92][93][94] In general, studies assessing the utility of NIRS in moderate/severe TBI are limited, as highlighted in a recent systematic review on the topic. 79 NIRS-based CA metrics do closely co-vary with standard ICP-derived versions.…”
Section: Cerebral Autoregulation Monitoring and "Other" Multi-modal M...mentioning
confidence: 99%